ROLA REFERENDUMW TRANSFORMACJACH USTROJOWYCH - Krzywoszyński, Przemysław (Zeszyty Prawnicze, 2016)
THE ROLE OF A REFERENDUM IN CONSTITUTIONAL TRANSFORMATIONS Summary The aim of this paper is a summary of discussion on the use of a nationwide referendum, which was held in the 80’s and 90’s of the 20th century and the current criticism of the institution. The nationwide referendum was the basic form of direct democracy and constituted an accurate reflection of social will towards the end of the 20th century. Nowadays because of surprising results of referendums in the Western democracies and its controversial usage in non-democratic countries the opinions on post-democratic era emerge. The institution of referendum is facing strong criticism. The opponents of referendum, citing the technological breakthrough, call for major reform of the procedures of direct democracy in order to adapt them to the needs of modern computerized society.